Dynamic behavior of Josephson-junction qubits: crossover between Rabi oscillations and Landau–Zener transitions - Shevchenko, S.N.; Kiyko, A.S.; Omelyanchouk, A.N.; Krech, W. (Физика низких температур, 2005)
We study the dynamic behavior of a quantum two-level system with periodically varying parameters
by solving numerically the master equation for the density matrix. Two limiting cases are
considered: multiphoton Rabi oscillations and Landau–Zener transitions. The approach is applied
to the description of the dynamics of superconducting qubits. In particular, the case of the interferometer-
type charge qubit with periodically varying parameters (gate voltage or magnetic flux)
is investigated. The time-averaged energy level populations are calculated as functions of the
qubit’s control parameters.